Chapter Dalla geografia storica all'archeologia del paesaggio e dell'ambiente. Una irrinunciabile eredità di Massimo Quaini - Panetta, Alessandro (Territori, 2021)
This contribution discusses the legacy of Massimo Quaini's research in the field of postclassical rchaeology and, in particular, in the study of landscape and environment. Its active participation in the archaeological theoretical debate is highlighted through the analysis of his bibliography and experiences from the 70's until his last works with the Territorialist Society and the Laboratory of Environmental Archaeology and History (LASA) of the University of Genoa.